A Mitochondria-Associated Oxidative Stress Perspective on Huntington’s Disease - Zheng, Ju; Winderickx, Joris; Franssens, Vanessa; Liu, Beidong (Frontiers in Molecular Neuroscience, 2018)
Huntington’s disease (HD) is genetically caused by mutation of the HTT gene. At present, the mechanisms underlying the defect of HTT and the development of HD remain largely unclear. However, increasing evidence shows the presence of enhanced oxidative stress in HD patients. In this review, we focus on the role of oxidative stress in the pathogenesis of HD and discuss mediators and potential mechanisms involved in mutant Huntingtin (HTT)-mediated oxidative stress generation and progression. Furthermore, we emphasize the role of the unicellular organism Saccharomyces cerevisiae in investigating mutant HTT-induced oxidative stress. Overall, this review provides an overview of the latest findings regarding oxidative stress in HD and potential therapeutic targets for HD.